Actinomortierella wolfii: Identity and pathology - L.S.M. Sigera; Sarah A. Ahmed; Abdullah M.S. Al-Hatmi; P.G.R.U.M. Welagedara; P.I. Jayasekera; Sybren de Hoog (Medical Mycology Case Reports, 2022)
Actinomortierella wolfii (Mortierellales), formerly Mortierella wolfii, is a causative agent of bovine systemic infection and abortion. Human infections caused by this species are extremely rare. Here, we present a case of a patient with B-Cell Acute Lymphoblastic Leukemia (B-ALL) who was diagnosed with a rhinocerebral infection caused by this fungus. Amphotericin treatment of the patient proved unsuccessful. This type of disease is otherwise nearly exclusively limited to members of the order Mucorales. The taxonomy of the causative agent is discussed.